Michelangelo's world - Ventura, Piero (New York : G.P. Putnam's Sons, 1988)
Recounts the life of the famous sculptor, painter, poet, and architect who flourished during the Italian Renaissance.
Translation of: Io Michelangelo.
Children's Catalog (Wilson)
Junior High School Library Catalog (Wilson)
Child Study Children's Book Committee
6.2
5-8
Keywords: Michelangelo Buonarroti, -- 1475-1564 -- Juvenile literature; Michelangelo Buonarroti, -- 1475-1564.; Michelangelo Buonarroti, -- 1475-1564.; Artists -- Italy -- Biography -- Juvenile literature; Artists; Artists, Italian -- Biography